Examining the wider context of formal youth mentoring programme development, delivery and maintenance: A qualitative study with mentoring managers and experts in the United Kingdom. (December 2018) - Busse, Heide; Campbell, Rona; Kipping, Ruth
Abstract: Mentoring programmes are commonplace, yet little is known about the circumstances in which they operate. This study aimed to gain insight into the context surrounding youth mentoring programmes by asking programme managers and experts in the United Kingdom about their experiences. Telephone interviews with twenty-three programme managers and five experts were undertaken. Interviews were recorded, transcribed verbatim and analysed iteratively using thematic analysis. Contextual influences at the individual-, interpersonal-, organisational-, community-, policy-, and societal-level were identified to impact on programme's development, delivery and maintenance and were summarised in a model. This study further found that youth mentoring programmes operate within a complex context. This context provides challenges and opportunities that impact on programme's sustainability; resulting in many externally-funded programmes to 'hang by a thread'. It is important for service providers, commissioners and academics to recognise the complexity surrounding mentoring programmes to ensure that programmes are delivered as intended and evaluated appropriately. Highlights: Formal mentoring programmes in the United Kingdom operate within a complex context Individual-, interpersonal-, organisational-, community-, policy-, and societal-level influences were identified A conceptual model was established highlighting the range of contextual influences on formal mentoring programmes The context provides challenges and opportunities that impact on programme's sustainability